Wali Nikah dalam Pembacaan Ulama dan Perundang-Undangan (Menelusuri Nilai-Nilai Filosofis Dari Peran Wali Nikah) - NUR FAIZAH (Proceedings of Annual Conference for Muslim Scholars, 2017)
In the marriage law in Indonesia, the guardian (wali) becomes very complicated issue. It is certainly not out of the understanding of the scholars, both conventional scholars, contemporary or legislation. Because the arguments are held down by both the Qur'an and hadith still interpretable. Although the validity of guardians according to scholars and the reading of legislation is very diverse, the majority of Muslims still requires a guardian of marriage even if it will be able to fertilize the patriarchal practices. But despite it all, there are values that are contained behind the role of guardian. Among other things, the value of the benefit, equality, consultation, wisdom, freedom, justice and prosperity.